2023
DOI: 10.3389/fmed.2023.1116912
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Successful outcome of a young patient with rhabdomyolysis and shock caused by diquat poisoning

Abstract: The widespread use of diquat as a substitute for paraquat has led to an increase in poisoning deaths. A successful case of diquat poisoning complicated with rhabdomyolysis and shock was lacking. A 13-year-old previously healthy girl ingested 40 ml of diquat solution in a suicide attempt. The concentration of diquat in serum was 436.2 ug/L at 10 h after poisoning. The clinical course was characterized by progressive multi-organ dysfunction, particularly rhabdomyolysis and shock. The main treatments included int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Additionally, the eGFR was significantly lower in the deceased group ( P < 0.01), and there was a significantly greater number of patients with abnormal BP. A systemic inflammatory response may occur in patients with DQ [ 16 ]. Previous studies have also reported a close association between early elevation of WBC and adverse prognosis, suggesting that WBC may serve as a prognostic factor, as confirmed by the present study [ 5 , 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the eGFR was significantly lower in the deceased group ( P < 0.01), and there was a significantly greater number of patients with abnormal BP. A systemic inflammatory response may occur in patients with DQ [ 16 ]. Previous studies have also reported a close association between early elevation of WBC and adverse prognosis, suggesting that WBC may serve as a prognostic factor, as confirmed by the present study [ 5 , 10 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a strong, graded, and independent correlation between RDW and eGFR [ 21 ]. Clinically, ADP patients are characterized by multiorgan damage, primarily involving the kidneys and central nervous system [ 17 ], and some patients have complications such as anemia [ 24 ], systemic inflammatory reactions [ 16 ], and acute respiratory distress syndrome [ 5 ] in the later stages. Glomerular filtration rate is the rate at which plasma is filtered to produce ultrafiltrate.…”
Section: Discussionmentioning
confidence: 99%